2012
DOI: 10.1016/j.fob.2012.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of N‐ and O‐linked mannosyltransferase genes is modulated by the pacC gene in the human dermatophyte Trichophyton rubrum

Abstract: In fungi, ambient pH sensing involves the activation of the Pal/PacC signalling pathway. In the dermatophyte Trichophyton rubrum, pH-dependent secretion of keratinases, which are major virulence determinants, is affected by disruption of the pacC gene. Here, the transcription profiling of the genes coding for N- and O-linked mannosyltransferases, enzymes involved in protein glycosylation, was evaluated in T. rubrum in response to disruption of the pacC gene and growth in keratin, glucose, and glucose plus glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
3
13
0
2
Order By: Relevance
“…In addition, by using an mRNA differential display, we isolated one cDNA, not detected in the palB7 strain, that encodes a manosyltransferase . In Trichophyton rubrum , disruption of the pacC gene resulted in decreased growth on human nails and decreased secretion of keratinolytic proteases possibly through transcriptional modulation of the O‐ and N‐linked mannosyltransferase genes . Transcription profiling of these two mannosyltransferases revealed a high level of complexity because their transcription were also affected by nutrients, culture pH, and the functioning of the pacC gene .…”
Section: Is Proteolysis Of the Transcription Regulator Pacc Imperativmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, by using an mRNA differential display, we isolated one cDNA, not detected in the palB7 strain, that encodes a manosyltransferase . In Trichophyton rubrum , disruption of the pacC gene resulted in decreased growth on human nails and decreased secretion of keratinolytic proteases possibly through transcriptional modulation of the O‐ and N‐linked mannosyltransferase genes . Transcription profiling of these two mannosyltransferases revealed a high level of complexity because their transcription were also affected by nutrients, culture pH, and the functioning of the pacC gene .…”
Section: Is Proteolysis Of the Transcription Regulator Pacc Imperativmentioning
confidence: 99%
“…In Trichophyton rubrum , disruption of the pacC gene resulted in decreased growth on human nails and decreased secretion of keratinolytic proteases possibly through transcriptional modulation of the O‐ and N‐linked mannosyltransferase genes . Transcription profiling of these two mannosyltransferases revealed a high level of complexity because their transcription were also affected by nutrients, culture pH, and the functioning of the pacC gene . We hypothesized that putative pal ‐dependent PacC post‐translational modifications are determinants for the conversion of PacC to its functional form, irrespective of ambient pH, in which the active PacC protein should carry the post‐translational modification promoted by the pal ‐signaling cascade.…”
Section: Is Proteolysis Of the Transcription Regulator Pacc Imperativmentioning
confidence: 99%
“…However, this zoophilic dermatophyte can be transmitted to humans through direct contact with infected animal via arthrospores 1 . A keratinolytic activity and pathogenesis of this group of medically important fungi is corelated because, during infection, dermatophytes secrete a lot of proteases that degrade keratinised structures into oligopeptides as well as free amino acids, which are then used by the fungi as sources of nutrients 2 . Proteolytic degradation of keratin is possible after relaxation of its structure by reduction of disulphide bridges (S–S).…”
Section: Introductionmentioning
confidence: 99%
“…Using mutant strains carrying the Δ pac-3 (or rim101 / pacC ) revealed that the PAC-3 transcription factor correlates with fungal traits beyond pH signaling, impacting fundamental biological processes, including cell morphology, hyphae growth, conidiation, and adaptation to the host or nutritional variances ( Ferreira-Nozawa et al , 2006 ; Mendes et al , 2012 ; O'Meara et al , 2014 ; Martins et al , 2018 , 2019 ; Rascle et al , 2018 ). In Neurospora crassa , the deletion of pac-3 and the pal cascade-associated genes, except for Δ pal-9 / palI, diminished aerial growth, reduced conidiation, and resulted in high production of melanin, in comparison with that in the wild-type strain ( Virgilio et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of pac-3 / rim101 / pacC is modulated in response to environmental conditions, including variations in inorganic phosphate (Pi), carbon sources, and pH fluctuations, which may impair critical physiological functions ( Ferreira-Nozawa et al , 2006 ; Trevisan et al , 2011 ; Mendes et al , 2012 ; Martins et al , 2019 ). In this study, we used RNA-seq analysis to assess the genes related to morphogenesis and development of the N. crassa mutant Δ pac-3 cultivated in media containing sufficient or limited Pi, an essential constituent of biomolecules ( Gras et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%